The influence of fetal sex on antenatal maternal glucose and insulin dynamics - Mullins, Thomas P.; Gallo, Linda A.; McIntyre, H. David; Barrett, Helen L. (Frontiers in Clinical Diabetes and Healthcare, 2024)
The ‘Developmental Origins of Health and Disease’ (DOHaD) hypothesis postulates that exposures during critical periods of development and growth, including maternal hyperglycemia, can have significant consequences for short- and long-term health in offspring. The influence of fetal status on maternal (patho)physiology is less well understood but gaining attention. Fetal sex specifically may be an independent risk factor for a range of adverse pregnancy outcomes, including increased gestational diabetes mellitus (GDM) frequency with male fetuses in multi-ethnic populations. Fetal sex has been thought to modulate maternal glucose metabolism, including insulin dynamics, through complex genetic and hormonal interactions. Mechanisms have not been fully elucidated, however, but may relate to sexual dimorphism in maternal-fetal-placental interactions. We review current evidence on the potential influence of fetal sex on maternal glucose and insulin dynamics, and fetal outcomes.